Antistatic protective film

By dispersing a blended resin with core-shell structure antistatic agent in the core layer of the antistatic protective film, combined with the first random copolymerized polypropylene resin, the pollution problem caused by the migration of the antistatic agent is solved, and the antistatic protective film is realized permanent antistatic properties and stable effects.

CN119463723APending Publication Date: 2025-02-18ZHEJIANG JIEMEI ELECTRONICS & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411738083.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The migration of antistatic agents in existing antistatic protective films leads to product contamination, and the antistatic effect gradually decreases or disappears with time and environment changes.

Method used

Using a blended resin with core-shell structure antistatic agent dispersed in the polypropylene resin, combined with the first random copolymerized polypropylene resin, the core-shell structure antistatic agent is uniformly dispersed to form a conductive path, preventing its migration and improving antistatic properties. .

Benefits of technology

The permanent antistatic properties of the antistatic protective film are realized, preventing contamination of products, and the antistatic effect is stable and does not decrease with time or environment changes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005161959330000081
    Figure BDA0005161959330000081
  • Figure BDA0005161959330000091
    Figure BDA0005161959330000091
Patent Text Reader

Abstract

The invention belongs to the technical field of protective films, and particularly relates to an antistatic protective film which sequentially comprises a self-adhesive layer, a core layer and a surface layer, the core layer comprises antistatic resin and first random copolymer polypropylene resin, and the antistatic resin is blended resin formed by dispersing a core-shell structure antistatic agent in polypropylene resin; the core of the antistatic agent with the core-shell structure is metal nanoparticles, and the shell of the antistatic agent with the core-shell structure is an inorganic substance. According to the antistatic protective film disclosed by the invention, the polypropylene blend resin dispersed with the core-shell structure antistatic agent is added to the core layer, so that the core-shell structure can be uniformly dispersed in the antistatic protective film, a conductive path in fine layered or rib-shaped distribution is formed, and the antistatic protective film is good in chemical stability, not easy to migrate and volatilize and permanent in antistatic property; and the antistatic effect cannot be gradually reduced or disappeared along with time lapse and environment change.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of protective films, and in particular relates to an antistatic protective film. Background Art

[0002] With the continuous development of electronic technology, LED backlight modules are increasingly used in liquid crystal display devices. LED backlight modules are mainly composed of light sources, light guide plates, optical films, etc. During the assembly and use of LED backlight modules, protective films are widely used for surface protection of products. However, ordinary protective films are prone to generate static electricity during use, causing damage to sensitive electronic components, affecting product quality, and even causing safety hazards. Therefore, it is of great practical significance to develop a protective film with antistatic properties.

[0003] In order to solve the static electricity problem of the protective film, an antistatic agent is usually added to the protective film. For example, the patent with publication number CN111440556B discloses a protective film and its preparation method, which includes a surface layer, a core layer and an adhesive layer from top to bottom; the surface layer includes 97-99.5% of polypropylene resin and 0.5-3% of an opening agent; the core layer includes 100% of polypropylene resin; the adhesive layer includes 60-82% of a styrene-based thermoplastic elastomer, 15-39% of a polyolefin resin and 1-3% of an antistatic agent; the antistatic agent used is selected from a mixture of polyether amide and glycerol ester, so as to solve the problem that a large amount of static electricity is easily generated between the adhesive layer of the protective film and the surface of the optical film during the process of tearing the existing protective film from the optical film.

[0004] The antistatic agent used above is a surfactant antistatic agent, and its working principle is to use the mixture of polyetheramide and glycerol ester to form a lubricating film on the film surface, reduce the friction coefficient between the film and the product, and reduce the charge generated by friction. Although it has a certain antistatic effect, its antistatic performance is unstable, especially in a high temperature environment, the molecular thermal motion is intensified, the activity of the molecules in the mixture of polyetheramide and glycerol ester is enhanced, and it is easy to migrate and volatilize, resulting in contamination of the product surface. The antistatic effect will gradually decrease or disappear with the passage of time and environmental changes. Summary of the invention

[0005] The purpose of the present invention is to provide an antistatic protective film which has permanent antistatic properties and will not migrate to cause product contamination, so as to solve the problems that the antistatic agent in the existing antistatic protective film migrates to cause product contamination and the antistatic effect gradually decreases or disappears with the passage of time and environmental changes.

[0006] The present invention adopts the following technical solution:

[0007] An antistatic protective film comprises a self-adhesive layer, a core layer and a surface layer in sequence, wherein the core layer comprises an antistatic resin and a first random copolymer polypropylene resin, the antistatic resin is a blended resin in which a core-shell structure antistatic agent is dispersed in the polypropylene resin; the core of the core-shell structure antistatic agent is a metal nanoparticle and the shell is an inorganic substance.

[0008] The antistatic protective film adds a polypropylene blended resin dispersed with a core-shell structure antistatic agent to the core layer, uses the polypropylene resin as a carrier, and has high compatibility with the first random copolymer polypropylene resin, so that the core-shell structure antistatic agent is evenly dispersed in the antistatic protective film to form a conductive path with a fine layered or ribbed distribution, so that the static charge can be conducted and dissipated through these paths to reduce the accumulation of static electricity, and the conductive path is relatively stable inside the core layer and will not be easily destroyed or changed, so as to achieve permanent and excellent antistatic properties. In addition, the polypropylene resin and the first random copolymer polypropylene resin will be entangled with each other after mixing, hindering the free movement of the core-shell structure, making it difficult to migrate from the inside of the core layer to the surface or diffuse to other areas, preventing contamination of the product, and the antistatic effect of the protective film will not gradually decrease or disappear over time and environmental changes.

[0009] Preferably, the core layer comprises 5wt%-35wt% of the antistatic resin and 65wt%-95wt% of the first random copolymerized polypropylene resin, so that the tearing voltage of the antistatic protective film is ≤4kv, and has excellent antistatic effect. When the content of the antistatic resin is less than 5wt%, the tearing voltage of the antistatic protective film will be greater than 4kv, and when the content of the antistatic resin is greater than 35wt%, the antistatic property of the antistatic protective film will not increase, which is not conducive to cost control.

[0010] Preferably, the density of the polypropylene resin is 0.900-0.940 g / cm 3 , melt index is 6-13g / 10min, and it has excellent processability.

[0011] Preferably, the metal nanoparticles are silver nanoparticles or copper nanoparticles. In terms of conductivity, silver nanoparticles are preferred.

[0012] Preferably, the inorganic substance is silicon dioxide or aluminum oxide. Silicon dioxide has excellent chemical stability and is not prone to chemical reaction under most environmental conditions, which enables the antistatic agent with it as a shell to maintain structural stability in different application scenarios and will not be easily degraded or deteriorated due to environmental factors. And the core-shell structure formed by silicon dioxide and metal nanoparticles has good compatibility with polypropylene resin, which can increase the interface compatibility and adhesion between the core-shell structure antistatic agent and the polypropylene resin, effectively preventing the agglomeration of the core-shell structure antistatic agent, so that it is evenly dispersed in the polypropylene resin carrier, so silicon dioxide is preferred.

[0013] Preferably, the content of the core-shell antistatic agent is 5-25 parts by mass relative to 100 parts by mass of the polypropylene resin, so as to ensure sufficient antistatic properties without affecting the processability and haze of the protective film.

[0014] Preferably, the density of the first random copolymer polypropylene resin is 0.900-0.910 g / cm 3 , melt index is 5-10g / 10min, and it has excellent processability.

[0015] Preferably, the self-adhesive layer comprises 5wt%-20wt% of component A and 80wt%-95wt% of component B, wherein component A is a polyolefin elastomer, and component B is one or more of low-density polyethylene and TPO thermoplastic elastomer, and the initial adhesion of the antistatic protective film is controlled within a suitable range.

[0016] Preferably, the polyolefin elastomer is a random copolymer elastomer of ethylene and high carbon α-olefin, with a density of 0.850-0.880 g / cm 3 , the melt index is 5-30g / 10min, the α-olefin can be 1-butene, 1-hexene, 1-octene, etc., which can maintain good elasticity and flexibility in low temperature environment, will not become brittle and hard due to temperature reduction, and has excellent processability.

[0017] Preferably, the density of the low-density polyethylene is 0.910-0.960 g / cm 3 , melt index is 4-25g / 10min, and has excellent processability.

[0018] Preferably, the density of the TPO thermoplastic elastomer is 0.850-0.920 g / cm 3 , melt index is 3-20g / 10min, and it has excellent processability.

[0019] Preferably, the surface layer comprises 100% of a second random copolymerized polypropylene resin having a density of 0.900-0.930 g / cm 3 , melt index is 5-15g / 10min, and it has excellent processability.

[0020] Preferably, the core layer thickness of the antistatic protective film accounts for 65-82% of the overall thickness, the self-adhesive layer thickness accounts for 8-15% of the overall thickness, and the surface layer thickness accounts for 10%-20% of the overall thickness, so that the antistatic protective film has excellent comprehensive performance in optical properties, antistatic properties, initial adhesion and physical properties.

[0021] The core-shell antistatic agent can be prepared by a physical coating method, where metal nanoparticles and inorganic substances are ground and coated using a mechanical ball milling method. Specifically, a planetary ball mill is used for 5 hours at a ball milling speed of 500 rpm, and the ball-to-material ratio is 10:1. The ratio of metal nanoparticles to inorganic substances is not limited, and is based on the coating effect. It can be preferably that the metal nanoparticles and inorganic substances are matched in a mass ratio of 1:3 to 1:1.

[0022] The above-mentioned antistatic resin can be prepared by a twin-screw extrusion process of a core-shell structure antistatic agent and a polypropylene resin, and can fully and evenly mix the core-shell structure inorganic matter and the polypropylene resin. In the twin-screw extrusion process, key parameters include extrusion temperature, screw speed, feeding speed, etc. The extrusion temperature should be determined according to the melting point of the polypropylene resin and the stability of the core-shell structure antistatic agent, generally between 180-230°C. The screw speed and extrusion volume are adjusted according to the equipment selection. Taking the 65 model 600rpm equipment as an example, the screw speed is set to 200-300rpm and the feeding rate is 180-260kg / h to ensure uniform conveying and mixing of materials, while avoiding excessive shearing and overheating that affect product quality.

[0023] The antistatic surface protection film is prepared by co-extruding the self-adhesive layer composition, the core layer composition and the surface layer composition in a molten state in a three-layer co-extrusion casting manner.

[0024] By implementing the above technical solution, the present invention has the following beneficial effects:

[0025] The antistatic protective film of the present invention adds a polypropylene blended resin dispersed with a core-shell structure antistatic agent in the core layer, so that the core-shell structure can be evenly dispersed in the antistatic protective film and form a conductive path with fine layered or ribbed distribution. The antistatic protective film has good chemical stability, is not easy to migrate and volatilize, has permanent antistatic properties, and the antistatic effect will not gradually decrease or disappear with the passage of time and environmental changes.

[0026] The present invention further optimizes the composition ratio of the surface layer, the core layer and the self-adhesive layer, so that the performance of the antistatic protective film is further optimized and improved, and the film tearing voltage is ≤4kv, the initial adhesion is 4-6g, and the haze is 40-50%. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below through specific examples.

[0028] This specific embodiment is merely an explanation of the present invention and is not a limitation of the present invention. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed. However, as long as they are within the scope of the claims of the present invention, they are protected by the patent law.

[0029] The raw materials involved in the following examples are as follows:

[0030] Polypropylene resin: manufactured by LyondellBasell, RP229N.

[0031] The first random copolymer polypropylene resin: manufactured by Hanwha Total Petrochemical, BI305.

[0032] Second random copolymer polypropylene resin: manufactured by Hanwha Total Petrochemical, BF308.

[0033] Polyolefin elastomer: made by Dow Chemical, 5545.

[0034] Low-density polyethylene: manufactured by CNOOC Shell Petrochemical, 2420K.

[0035] TPO thermoplastic elastomer: manufactured by ExxonMobil, 3980FL.

[0036] Core-shell antistatic agent:

[0037] No. 1: Silver nanoparticles and silicon dioxide were mixed in a mass ratio of 1:1, and then ground and coated using a mechanical ball milling method, specifically using a planetary ball mill at a ball milling speed of 500 rpm for 5 hours, with a ball-to-material ratio of 10:1.

[0038] No. 2: Silver nanoparticles and aluminum oxide were mixed at a mass ratio of 1:2, and then ground and coated using a mechanical ball milling method, specifically using a planetary ball mill at a ball milling speed of 500 rpm for 5 hours, with a ball-to-material ratio of 10:1.

[0039] No. 3: Copper nanoparticles and silicon dioxide were mixed in a mass ratio of 1:1, and then ground and coated using a mechanical ball milling method, specifically using a planetary ball mill at a ball milling speed of 500 rpm for 5 hours, with a ball-to-material ratio of 10:1.

[0040] No. 4: Copper nanoparticles and aluminum oxide were mixed in a mass ratio of 1:2, and then ground and coated using a mechanical ball milling method, specifically using a planetary ball mill at a ball milling speed of 500 rpm for 5 hours, with a ball-to-material ratio of 10:1.

[0041] Antistatic resin:

[0042] No. A: No. 1 core-shell antistatic agent and polypropylene resin (mass ratio 5:100) are prepared by twin-screw extrusion process.

[0043] No. B: No. 2 core-shell structure antistatic agent and polypropylene resin (mass ratio 5:100) are prepared by twin-screw extrusion process.

[0044] No. C: No. 3 core-shell antistatic agent and polypropylene resin (mass ratio 5:100) are prepared by twin-screw extrusion process.

[0045] No. D: No. 4 core-shell antistatic agent and polypropylene resin (mass ratio 5:100) were prepared by twin-screw extrusion process.

[0046] No. E: No. 1 core-shell antistatic agent and polypropylene resin (mass ratio 10:100) are prepared by twin-screw extrusion process.

[0047] No. F: No. 1 core-shell antistatic agent and polypropylene resin (mass ratio 25:100) are prepared by twin-screw extrusion process.

[0048] The extrusion temperature should be determined according to the melting point of the polypropylene resin and the stability of the core-shell structure antistatic agent. In this embodiment, the extrusion temperature is 180-230° C. The screw speed and extrusion volume are adjusted according to the equipment selection. In this embodiment, the screw speed is set to 200-300 rpm and the feeding rate is 180-260 kg / h (65-type twin-screw extruder).

[0049] Example 1

[0050] This embodiment provides an antistatic protective film, which comprises a self-adhesive layer, a core layer and a surface layer in sequence, wherein the core layer comprises 20wt% of an antistatic resin and 80wt% of a first random copolymerized polypropylene resin. The antistatic resin is a No. A antistatic resin.

[0051] The self-adhesive layer includes 20 wt % of polyolefin elastomer, 60 wt % of low-density polyethylene and 20 wt % of TPO thermoplastic elastomer.

[0052] The skin layer includes 100% of a second random copolymer polypropylene resin.

[0053] Example 2

[0054] This embodiment provides an antistatic protective film, which comprises a self-adhesive layer, a core layer and a surface layer in sequence, wherein the core layer comprises 25wt% of an antistatic resin and 75wt% of a first random copolymerized polypropylene resin. The antistatic resin is a No. A antistatic resin.

[0055] The self-adhesive layer includes 20 wt % of polyolefin elastomer, 60 wt % of low-density polyethylene and 20 wt % of TPO thermoplastic elastomer.

[0056] The skin layer includes 100% of a second random copolymer polypropylene resin.

[0057] Example 3

[0058] This embodiment provides an antistatic protective film, which comprises a self-adhesive layer, a core layer and a surface layer in sequence, wherein the core layer comprises 35wt% of an antistatic resin and 65wt% of a first random copolymerized polypropylene resin. The antistatic resin is a No. A antistatic resin.

[0059] The self-adhesive layer includes 20 wt % of polyolefin elastomer, 60 wt % of low-density polyethylene and 20 wt % of TPO thermoplastic elastomer.

[0060] The skin layer includes 100% of a second random copolymer polypropylene resin.

[0061] Example 4

[0062] This embodiment provides an antistatic protective film, which comprises a self-adhesive layer, a core layer and a surface layer in sequence, wherein the core layer comprises 5wt% of an antistatic resin and 95wt% of a first random copolymerized polypropylene resin. The antistatic resin is a No. A antistatic resin.

[0063] The self-adhesive layer includes 20 wt % of polyolefin elastomer, 60 wt % of low-density polyethylene and 20 wt % of TPO thermoplastic elastomer.

[0064] The skin layer includes 100% of a second random copolymer polypropylene resin.

[0065] Example 5

[0066] The difference between this embodiment and embodiment 1 is that the antistatic resin adopts antistatic resin No. B.

[0067] Example 6

[0068] The difference between this embodiment and embodiment 1 is that the antistatic resin adopts antistatic resin No. C.

[0069] Example 7

[0070] The difference between this embodiment and embodiment 1 is that the antistatic resin adopts D-type antistatic resin.

[0071] Example 8

[0072] The difference between this embodiment and embodiment 1 is that the antistatic resin adopts E-grade antistatic resin.

[0073] Example 9

[0074] The difference between this embodiment and embodiment 1 is that the antistatic resin adopts antistatic resin No. F.

[0075] Example 10

[0076] The difference between this embodiment and embodiment 1 is that the self-adhesive layer includes 10 wt % of polyolefin elastomer, 80 wt % of low-density polyethylene and 10 wt % of TPO thermoplastic elastomer.

[0077] Embodiment 11

[0078] The difference between this embodiment and embodiment 1 is that the self-adhesive layer includes 20 wt % of polyolefin elastomer and 80 wt % of low-density polyethylene.

[0079] The antistatic surface protection film in each of the above embodiments is prepared by coextruding the above self-adhesive layer composition, core layer composition and surface layer composition in a molten state in a three-layer coextrusion casting manner, with a thickness of 5 μm for the self-adhesive layer, 40 μm for the core layer and 5 μm for the surface layer.

[0080] Example 12

[0081] The difference between this embodiment and embodiment 1 is that the thickness of each layer of the antistatic protective film is different, with the thickness of the self-adhesive layer being 7.5 μm, the core layer being 32.5 μm, and the surface layer being 10 μm.

[0082] Example 13

[0083] This embodiment provides an antistatic protective film, which comprises a self-adhesive layer, a core layer and a surface layer in sequence, wherein the core layer comprises 40wt% of an antistatic resin and 60wt% of a first random copolymerized polypropylene resin. The antistatic resin is a No. A antistatic resin.

[0084] The self-adhesive layer includes 30 wt % of polyolefin elastomer, 50 wt % of low-density polyethylene and 20 wt % of TPO thermoplastic elastomer.

[0085] The skin layer includes 100% of a second random copolymer polypropylene resin.

[0086] Embodiment 14

[0087] This embodiment provides an antistatic protective film, which comprises a self-adhesive layer, a core layer and a surface layer in sequence, wherein the core layer comprises 20wt% of an antistatic resin and 80wt% of a first random copolymerized polypropylene resin. The antistatic resin is a No. A antistatic resin.

[0088] The self-adhesive layer includes 30 wt % of polyolefin elastomer, 50 wt % of low-density polyethylene and 20 wt % of TPO thermoplastic elastomer.

[0089] The skin layer includes 100% of a second random copolymer polypropylene resin.

[0090] Embodiment 15

[0091] This embodiment provides an antistatic protective film, which comprises a self-adhesive layer, a core layer and a surface layer in sequence, wherein the core layer comprises 45wt% of an antistatic resin and 55wt% of a first random copolymerized polypropylene resin. The antistatic resin is a No. A antistatic resin.

[0092] The self-adhesive layer includes 20 wt % of polyolefin elastomer, 60 wt % of low-density polyethylene and 20 wt % of TPO thermoplastic elastomer.

[0093] The skin layer includes 100% of a second random copolymer polypropylene resin.

[0094] Example 16

[0095] The difference between this embodiment and embodiment 1 is that the core layer includes 3 wt % of antistatic resin and 97 wt % of the first random copolymer polypropylene resin.

[0096] Comparative Example 1

[0097] The difference from Example 1 is that the antistatic agent is a mixture of 20 wt % polyether ester amide and 80 wt % glyceride.

[0098] Comparative Example 2

[0099] The difference from Example 1 is that the antistatic agent uses silver nanoparticles alone without being coated with silicon dioxide.

[0100] Comparative Example 3

[0101] The difference from Example 1 is that the antistatic resin is prepared by mixing No. 1 core-shell antistatic agent and SEBS (9557) in a mass ratio of 5:100 through a twin-screw extrusion process.

[0102] Comparative Example 4

[0103] The difference from Example 1 is that the core layer includes 20 wt % of antistatic resin and 80 wt % of polypropylene resin (RP229N).

[0104] Comparative Example 5

[0105] The difference from Example 1 is that the antistatic resin includes silver nanoparticles, silicon dioxide and polypropylene resin, which are mixed and prepared by a twin-screw extrusion process. That is, the silver nanoparticles and silicon dioxide are not coated.

[0106] Comparative Example 6

[0107] The difference from Example 1 is that the thickness is 10 μm for the self-adhesive layer, 29 μm for the core layer, and 11 μm for the surface layer.

[0108] In order to verify the influence of the scheme of the present invention on the performance of the protective film, the initial adhesion, film tearing voltage, tensile strength and haze of the protective films obtained in each embodiment and comparative example were tested. The test method is as follows. The test results are shown in Table 1.

[0109] Test method:

[0110] 1. The initial adhesion test method is:

[0111] The prepared surface protection film was cut into 25mm*20cm strips and pasted on an optical substrate PET with Ra of 0.015-0.040μm, and pressed back and forth 3 times with a 2kg rubber roller at 300mm / min, and placed at room temperature 23℃ for 20min, and then tested for 180° adhesion using a peel tester at a speed of 300mm / min, using the standard GB / T 2792-2014. The initial adhesion is obtained. The initial adhesion is also the initial adhesion of the adhesive layer of the surface protection film.

[0112] 2. The tearing voltage test method is:

[0113] The prepared protective film was cut into samples of 10cm*30cm, and placed at a temperature of 23℃±2℃ and a relative humidity of 50%±10% for 1 day and 30 days. According to the sample formation time atmosphere group 1 (immediate), group 2 (1 day), and group 3 (30 days), the above 3 groups of samples were respectively laminated on an optical substrate PET with Ra of 0.015-0.040μm, and a 5kg rubber roller laminator was used to press back and forth 3 times at 8m / min at a temperature of 23℃±2℃ and a relative humidity of 50%±10%. The protective film was torn off, and the tearing voltage of the above samples and the optical substrate PET sheet was tested using a Keyence static tester.

[0114] 3. The specific test method for tensile strength is:

[0115] An electronic tensile testing machine is used, and the reference standard is GB / T1040.3.

[0116] 4. The test method for haze is:

[0117] A haze meter was used, and the reference standard was GB / T 2410-2008.

[0118] Table 1 Test results of various embodiments and comparative examples

[0119]

[0120]

[0121] From the test results shown in Table 1, it can be seen that the protective films obtained in Examples 1-16 have a relatively low tearing voltage, and have excellent antistatic effects. Moreover, the instant tearing voltage, the tearing voltage after 1 day, and the tearing voltage after 30 days are all basically the same, and the antistatic sustainability is better, and the film has permanent antistatic properties. In particular, in Examples 1-12, the initial adhesion of the protective films obtained is between 4-6gf / 25mm, and the adhesion is appropriate. The instant tearing voltage, the tearing voltage after 1 day, and the tearing voltage after 30 days can all be maintained at 4kv or less, and the antistatic performance is more excellent, and the tensile strength and haze performance are also excellent.

[0122] Compared with Example 1, the antistatic agent in Comparative Example 1 adopts a mixture of 20wt% polyether ester amide and 80wt% glycerol ester. Although the initial adhesion of its protective film is comparable to that of the protective film of Example 1, the immediate film tearing voltage and the film tearing voltage after 1 day are both relatively large, especially the film tearing voltage after 30 days, which reaches 11.3kv, which is much larger than 3.3kv of Example 1.

[0123] Compared with Example 1, in Comparative Example 2, the antistatic agent directly uses silver nanoparticles without silicon dioxide coating. The silver nanoparticles alone cannot be evenly dispersed in the polypropylene resin, and agglomeration problems occur, resulting in poor antistatic effect and poor appearance, and more crystal points. Specifically, the tearing voltage increases significantly.

[0124] Compared with Example 1, in Comparative Example 3, the antistatic resin uses No. 1 core-shell antistatic agent and SEBS (9557), and no polypropylene resin is used in the antistatic resin, so that the core-shell antistatic agent cannot interact with the first random copolymer polypropylene resin to uniformly disperse in the antistatic protective film to form a conductive path with fine layered or ribbed distribution, so the antistatic performance is not ideal, and the film tearing voltage is too large. In addition, the use of SEBS will also lead to high viscosity, which further increases the film tearing voltage.

[0125] Compared with Example 1, the first random copolymer polypropylene resin is not used in the core layer of Comparative Example 4, and the processability is relatively poor, which affects the dispersibility. As a result, the tearing voltage of the protective film is also relatively large.

[0126] Compared with Example 1, although silver nanoparticles and silicon dioxide are added to the antistatic agent in Comparative Example 5, they are added directly without coating treatment. In this way, the silver nanoparticles cannot be evenly dispersed in the polypropylene resin, there is a problem of particle agglomeration, and the antistatic performance is significantly reduced.

[0127] Compared with Example 1, the thickness configuration ratio of each layer in Comparative Example 6 was changed, resulting in higher initial adhesion, difficulty in film tearing, and reduced antistatic performance, indicating that the thickness ratio between each layer also affects the performance of the protective film.

Claims

1. An antistatic protective film, comprising a self-adhesive layer, a core layer and a surface layer in sequence, characterized in that: The core layer comprises an antistatic resin and a first random copolymer polypropylene resin. The antistatic resin is a blended resin in which a core-shell structure antistatic agent is dispersed in polypropylene resin. The core of the core-shell structure antistatic agent is a metal nanoparticle and the shell is an inorganic substance.

2. The antistatic protective film according to claim 1, characterized in that: The core layer includes 5wt%-35wt% of antistatic resin and 65wt%-95wt% of first random copolymerized polypropylene resin.

3. The antistatic protective film according to claim 1, characterized in that: The content of the core-shell structure antistatic agent is 5-25 parts by mass relative to 100 parts by mass of the polypropylene resin.

4. The antistatic protective film according to claim 1, characterized in that: The density of the polypropylene resin is 0.900-0.940 g / cm 3 , the melt index is 6-13g / 10min.

5. The antistatic protective film according to claim 1, characterized in that: The density of the first random copolymer polypropylene resin is 0.900-0.910 g / cm 3 , the melt index is 5-10g / 10min.

6. The antistatic protective film according to claim 1, characterized in that: The metal nanoparticles are silver nanoparticles or copper nanoparticles.

7. The antistatic protective film according to claim 1, characterized in that: The inorganic substance is silicon dioxide or aluminum oxide.

8. The antistatic protective film according to claim 1, characterized in that: The self-adhesive layer comprises 5wt%-20wt% of component A and 80wt%-95wt% of component B, wherein component A is a polyolefin elastomer, and component B is one or more of low-density polyethylene and TPO thermoplastic elastomer.

9. The antistatic protective film according to claim 8, characterized in that: The polyolefin elastomer is a random copolymer elastomer of ethylene and high carbon α-olefin, with a density of 0.850-0.880 g / cm 3 , the melt index is 5-30g / 10min.

10. The antistatic protective film according to claim 1, characterized in that: The core layer thickness of the antistatic protective film accounts for 65-82% of the overall thickness, the self-adhesive layer thickness accounts for 8-15% of the overall thickness, and the surface layer thickness accounts for 10%-20% of the overall thickness.

Citation Information

Patent Citations

  • A protective film and its preparation method

    CN111440556B